The syndemic burden of HIV/AIDS in Africa amidst the COVID‐19 pandemic. Issue 1 (4th October 2021) - Uwishema, Olivier; Taylor, Charles; Lawal, Lukman; Hamiidah, Nakyanzi; Robert, Isoke; Nasir, Abdulrasheed; Chalhoub, Elie; Sun, Jeffrey; Akin, Burak T.; Adanur, Irem; Mwazighe, Rehema M.; Onyeaka, Helen
Abstract: Introduction: The human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) has long affected millions of individuals across the globe. Historically, the prevalence of this disease is particularly noted within the African continent. Before the coronavirus disease 2019 (COVID‐19) pandemic, many African countries struggled to effectively manage the increasing burden associated with HIV/AIDS. There is now a need to reassess this in a COVID‐19 pandemic context so that the impact of COVID‐19 on HIV/AIDS healthcare within Africa can be adequately evaluated. Methods: Data collection was performed on the PubMed, Ovid MEDLINE and Embase bibliographical databases with a predefined search strategy. Searches were performed in blind duplicate and all articles considering COVID‐19 and HIV/AIDS within African healthcare were considered. Results: The COVID‐19 pandemic has severely exacerbated the many issues surrounding HIV/AIDS care within many African countries. These impacts are noticeable in medical, psychological, and socio‐political contexts. Conclusions: Before efforts are made to improve the provision of HIV/AIDS and COVID‐19 care within Africa, it is important that this issue is brought to the attention of the scientific and clinical community so that the continent can receive the necessary support and aid.